MULTI DIGITAL LANGUAGE LEARNING IN MILLENNIAL STUDENT ENVIRONMENTS DURING COVID 19 PANDEMIC: THE EDUCATION SIDE - Arip Naksabandi (PROJECT (Professional Journal of English Education), 2022)
Nowadays, the education field has gigantic issues and a problem related to the situation and condition of the Covid-19 Pandemic. Teachers and students have a new challenge to face and should find out a new solution to prevent the learning loss cases. A lot of policies and ideas come up in order to solve the problem to support the educational activities through research and innovating technologies. Teachers and students must survive in this situation to make teaching and learning activity still happen and work well. A lot of innovative digital media and technology is used to face this situation, there are some famous digital applications and Social Networking Sites (SNSs) such as YouTube, Edmodo, Facebook, WhatsApp, Google Classroom, Zoom Cloud Meeting, Google Meet and another application or Social Networking Sites (SNSs). This study uses literature review study method in order to collect the data. All of the data in this study used secondary data and researcher collected from some articles, books and journals. From all of the data there are some digital platform and SNSs that commonly use in Millennial’s environment there are YouTube; Edmodo; Zoom Cloud Meeting; Google Services (Google Meet, Google Classroom, and Google Form); WhatsApp and Instagram. Keywords:  Multi Digital, Millennial Students, Education